Assessment practices in elementary education and school culture - Cianflone, Ana Raquel Lucato; Andrade, Érika Natacha Fernandes de (Paidéia (Ribeirão Preto), 2007)
The LDB 9.394/96, Lei de Diretrizes e Bases da Educação Nacional (Directives and Basis for the National Education), introduced important modifications in the organization and assessment practices adopted in Brazilian schools. In this context, the purpose of this study was to investigate the assessment practices that shape school culture and its ethos and also how these values give basis to and guide the pedagogical work. Considering the aims proposed, the qualitative investigation was used as a methodological support. The study was conducted in three state public elementary schools involving teachers, pedagogical coordinators and direction. The results indicate that there is a predominance of practices grounded on a sequencial system instead of a progressive one. Values associated to a selective school function and movements of resistance and of adjustment to the new purposes were noticed as follows: informal handling of student class transfers, precarious ordination of the assessments and the establishment.